2019
DOI: 10.1002/app.48385
|View full text |Cite
|
Sign up to set email alerts
|

Zinc chloride/acetamide deep eutectic solvent‐mediated fractionation of lignin produces high‐ and low‐molecular‐weight fillers for phenol‐formaldehyde resins

Abstract: Lignin readily dissolves in a deep eutectic solvent (DES) composed of ZnCl 2 /acetamide 1:3 M ratio in concentrations up to 16.7 wt %, and upon addition of water, two fractions were obtained; one composed of lignin with low-molecular weight that remained dissolved in the DES/water mixture, whereas the other fraction of lignin with higher molecular weight (regenerated lignin, RL) was regenerated by precipitation. Both the RL fraction and the whole solution of lignin in DES were used to replace part of phenol (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…DESs are often considered as a sub-class of ionic liquids; however, compared to traditional ionic liquids, DESs are of advantage due to its simple preparation, high abundance of raw materials, low price, environmental friendliness, and biodegradability. Previous DESs have also been used in the removal of lignin and fractionation of other components from biomasses [19][20][21][22][23] . It has been shown that DESs can be used for efficient lignin removal, in order to obtain a high-quality lignin [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DESs are often considered as a sub-class of ionic liquids; however, compared to traditional ionic liquids, DESs are of advantage due to its simple preparation, high abundance of raw materials, low price, environmental friendliness, and biodegradability. Previous DESs have also been used in the removal of lignin and fractionation of other components from biomasses [19][20][21][22][23] . It has been shown that DESs can be used for efficient lignin removal, in order to obtain a high-quality lignin [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…DESs are often considered as a subclass of ionic liquids; however, compared to traditional ionic liquids, DESs are of advantage due to its simple preparation, high abundance of raw materials, low price, environmental friendliness, and biodegradability. Previous DESs have also been used in the removal of lignin and fractionation of other components from biomasses. It has been shown that DESs can be used for efficient lignin removal in order to obtain a high-quality lignin. We previously used six different deep eutectic solvent (DES) treatmentsfive acidic (natural organic acid-choline chloride) and one alkaline (K 2 CO 3 -glycerol)to compare the delignification and nanofibrillation of agricultural byproducts . However, the properties of lignin fractions are known to be strongly associated with the chemical characteristics of used solvent systems; furthermore, the characteristics and differences of lignins separated using different DESs remain to be poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…DESs impacted the interaction between the intermolecular and intramolecular in the lignin network due to the action of the ionic environment, and the chemical structure of lignin was found to be influenced by Zn by comparing the FTIR spectra of lignin and relignin, where a similar conclusion was drawn by Sun et al [98]. Hong et al [54] compared the phenolic resins modified by lignin (LPF), DES/lignin (DLPF) and DES-modified lignin (MLPF) and reported that the curing time was in a trend of DLPF > MLPF >LPF. MLPF exhibited higher bond strength and shorter curing time than the phenolic resin.…”
Section: Phenolic Resinmentioning
confidence: 59%
“…Polycondensation of formaldehyde using this eutectic in the presence of iron acetate resulted in the creation of high surface area monoliths with graphitic character and very high electrical conductivity (up to 31 S cm −1 [ 89 ]). DES systems have also been prepared as catalysts for the polycondensation of furfuryl alcohol to ultimately produce porous carbon electrodes [ 87 ], as well for the effective solubilization of lignin to effectively incorporate biomass fillers into phenol-formaldehyde resins [ 92 ].…”
Section: Des Systems In Polymer and Materials Sciencementioning
confidence: 99%